Feasibility study on the setting up of Perwira Affin Bank Service Centre at ITM, Kota Samarahan / Felex Tomick - Tomick, Felex (1999)
This research attempts to study the feasibility of setting up one service centre of Perwira Affin Bank at Institut Teknologi Mara Cawangan Sarawak at Kota Samarahan. Being purely for academic purpose, this study tries to understand the need for banking and financial services among the respondents. The respondents or the target group for this project paper are the staff working at ITM and the students studying at ITM. Besides the main objective to study the feasibility of setting up Perwira Affin Bank service centre at Institut Teknologi Mara Cawangan Sarawak at Kota Samarahan, the other objectives of this study are to determine major types of banking facilities required by the respondents, to find out the potential of providing banking and financial services at ITM and to gather valuable information for recommendations to Perwira Affin Bank to spread its wing to Kota Samarahan.